Molecular Dynamic Study of Java Cardamom (Wurfbania compacta) Leaf Compounds Targeting Xanthine Oxidase for Antihyperuricemia - Ali Nofriyaldi; Nitya Nurul Fadilah; Selvy Isnaeni (Biology, Medicine, & Natural Product Chemistry, 2025)
Hyperuricemia is a disorder marked by elevated concentrations of uric acid in the bloodstream, which can trigger gout and other metabolic complications. Conventional therapies such as allopurinol are effective but often cause side effects. This study aims to explore the potential of bioactive compounds from cardamom leaves (Wurfbania compacta) as antihyperuricemic agents through an in silico approach. The methods used include mining phytochemical data from the literature, predicting pharmacokinetic properties and toxicity (ADMET), molecular docking as well as molecular dynamic. The screening results show that the compound with the most stable interaction from cardamom (Wurfbania compacta) with receptors that play a role in inhibiting xanthine oxidase enzyme in silico is the compound kaempferol with a Binding energy value of -8.1 kcal/mol and Ki 1.15 uM (micromolar). ADMET analysis indicates that the main candidate has a good pharmacokinetic profile and low toxicity potential. Based on the results of the RMSD and RMSF molecular dynamic analysis, the kaempferol compound shows a stable level of interaction and has 3 amino acid similarities with the comparison drug allopurinol, namely THR1010, VAL1011 and ALA1078, so it has the potential to be used as a candidate antihyperuricemia drug. These findings suggest that cardamom leaves have prospects as a source of natural antihyperuricemia compounds. Further in vitro and in vivo studies are needed to verify the biological activity and safety of its use.